Designing the WHO Safe Childbirth Checklist program to improve quality of care at childbirth. Issue 2 (3rd June 2013) - Spector, Jonathan M.; Lashoher, Angela; Agrawal, Priya; Lemer, Claire; Dziekan, Gerald; Bahl, Rajiv; Mathai, Matthews; Merialdi, Mario; Berry, William; Gawande, Atul A.
Abstract: Background: Poor‐quality care during institutional births in low‐ and middle‐income countries is a major contributing factor to preventable maternal and newborn harm, but progress has been slow in identifying effective methods to address these deficiencies at scale. Based on the success of checklist programs in other disciplines, WHO led the design and field testing of the WHO Safe Childbirth Checklist—a 29‐item tool that targets the major causes of maternal and newborn mortality globally. Methods: The development process consisted of comprehensive evidence and guideline review, in‐person consultation with content experts and other key stakeholders, iterative refinement through ongoing discussions with a wide collaborator network, and field evaluation for usability in 9 countries, primarily in Africa and Asia. Pilot testing in South India demonstrated major improvement in health workers' delivery of essential safety practices after introduction of the program. Results: WHO has launched a global effort to support further evaluation of the program in a range of contexts, and a randomized trial is underway in North India to measure the effectiveness of the program in reducing severe maternal, fetal, and newborn harm. Conclusion: A novel checklist program has been developed to support health workers in low‐resource settings to prevent avoidable childbirth‐related deaths.